PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, KOMITE AUDIT, KEPEMILIKAN MANAJERIAL, DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Irfan Fadholi Putra; Dirvi Surya Abbas; Imam Hidayat; Imas Kismanah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of institutional ownership, independent commissioners, audit committees, managerial ownership, and audit quality on the integrity of financial statements in service industry companies listed on the Indonesia Stock Exchange (IDX). The research period used is 5 years, namely the 2015-2021 period. The population of this study includes all service industry companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria, 7 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange. The analytical method used is multiple linear repression analysis using SPSS version 25 software. The results of the study show that partially the variables of Institutional Ownership and Audit Quality have no effect on the Integrity of Financial Statements, Independent Commissioners, Audit Committees, and Managerial Ownership have an influence on the Integrity of Financial Statements. Simultaneously, the variables of Institutional Ownership, Independent Commissioners, Audit Committees, Managerial Ownerships, and Audit Quality has an effect on the Integrity of Financial Statements.